La iniciación científica júnior y los conocimientos procedimentales en ciencias - Silva Holpert, Laura Nívea Rosa; Zompero, Andréia de Freitas (Góndola, enseñanza y aprendizaje de las ciencias, 2020)
This study aimed to ascertain evidences of investigative-type procedures in Science learning from students who participated in Junior Undergraduate Research Project. Among the procedures analyzed, the problem identification, the hypotheses issuing and the investigation planning were analyzed. The research was the qualitative type with a descriptive approach. 6 students from the 2nd year of the Certificate Program in Surveying Integrated to High School participated in the study. As a data collection instrument, three single problem-situation activities were applied during the execution of the Junior Undergraduate Research Project. The activities were intended to identify the understanding of a problem, the hypotheses issuing and the investigation planning. To analyze the data obtained, we used an instrument to assess the levels of investigative skills presented by students during the Junior Undergraduate Research Project. Before the results, comparing the performance of students in solving problem-situations, we could realize that students had best result in learning the investigative procedure of the investigation planning.